Factors that influence purchase intention towards proton cars / Mohd Zhafran Mohd Suhaili - Mohd Suhaili, Mohd Zhafran (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Sarawak, 2016)
Perusahaan Otomobil Nasional Berhad (PROTON) is one of the Malaysian automobile organizations that were established in 1983. Basically, Proton activities are to manufacture, assemble and sell motor vehicles and related products. In 1985, Proton has produced its first Malaysia car which is Proton Saga model. Proton Saga model has launched by the Malaysian Prime Minister, Dato' Seri Mahathir Mohamed. Dato' Seri Mahathir Mohamed is the person who had come with the idea of national car. The establishment of national car in nearly 3 decades ago and many things needs to be re-examined in order to make sure Proton can compete with other car brand in market. The main reason of this research is to investigate factors that influence customers purchase intention toward Proton cars. This is because, recently we can look from the report that released by Malaysian Automotive Association (MAA) shows that Proton ranks second best national car seller. There are four main factors that will be established in this research includes brand, price concern and value concern toward Proton products. Basically, these factors were believed to play a vital role in establishing overall perceptions of Malaysian customers toward the Proton car